The level of self-concept, school culture and school climate among student in Selangor - Abd Radzak, Sabarnur; Md Noor, Amna; MohdKhir, Azlina (Human Resource Management Academic Research Society, 2021)
The aim of the present study is to determine the level of self-concept, school culture and school climate among students in Selangor. This study involved 400 adolescents aged 14 and 16 years old from eight secondary schools in the state of Selangor. Respondents were selected through multi-stage cluster sampling. Data were collected using questionnaires through a self-administered procedure which are consists of social demographic background, school climate and school culture (Inventory of Parents and Peer Attachment (IPPA), Questions of Teacher’s Interaction (QTI),School Self-Review Tools (SSRT), Multidimensional Scale of Perceived Social SupportZimet) and self-concept (Self Concept—Individual Protective Factors Index). Overall, the level of self-concept, school culture and school climate are moderate among students in Selangor. The awareness of the influence and impact of self-concept, school culture and school climate involved in the adolescent development system is imperative. As a conclusion, adolescents' involvement in various self-development programs preventing them from engaging in delinquency activities thus safeguarding students’ psychosocial well-being. Suggested recommendations were discussed for future research of the present study.